Karya Tafsir Modern di Timur Tengah Abad 19 dan 20 M - Dalhari, Moh. (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
Motto that has always expressed is that the Koran was Sâlih li kull zamân wa makân, in the sense they do not just blindly accept what is revealed literally (as most commentators earlier), but try to understand by always trying to look at the context and meaning behind ayat- verses of the Koran. In other words, you want to search is the “spirit” or the moral message of the Koran itself. Modern interpretations are always encouraged to fit the paper with the condition of the interpreter. Advances in science may be the main factor in the birth and raise their interpreter responds. This paper tries to describe the state of some modern interpretations evolve. At the end of this paper, the authors conclude that the modern interpretation dominited by philosophy studies of the Koran, Koran and natural history. As well as newspapers and actual problems of Muslim Dailu. The authors also conclude that interpretations may exist in the modern era, when it contains a strong meaning for Muslims everyday problems (practical interpretation), as well as concrete and objective support for the development of human knowledge (tafsîr ‘ilmî).